UJI TOKSISITAS (Brine Shrimp Lethality Test) DAN AKTIVITAS HIPOGLIKEMIK DARI DAUN TERAP (Artocarpus odoratissimus B.) DENGAN METODE TOLERANSI GLUKOSA PADA MENCIT JANTAN - Nur Futihah; Harlinda Kuspradini (PROSIDING SEMINAR KIMIA, 2013)
Phytochemical, brine shrimp lethality and antibacterial activity tests of various fraction from terap leaf (Artocarpus odoratissimus B.) from Sungai Siring, East Samarinda has been carried out. Artocarpus odoratissimus B. bark was extracted with ethanol then concentrated by rotary evaporator. The total extract was fractioned with n-hexane, and ethyl acetate. Based on the secondary metabolites phytochemical test of the Artocarpus odoratissimus B. bark show that total extract and in various fraction is contain flavonoid and steroid. Brine Shrimp Lethality Test (BSLT) method used the shrimp larvas of Artemia salina Leach to study the mortality effect that caused by the leaves extracts of Artocarpus odoratissimus B.. The data obtained was analyzed by using SAS Probit analysis. Based on the LC 50 value from the result of BSLT method, the total extract and etil asetat with the highest toxicity is n-hexane extract. Hypoglicemic activity test was conducted using glucose tolerance to the mice. In this test, have shown that the most active fraction to lower blood glucose levels using a total extrac dose is 25 mg/kg BB with the percentage reduction in blood glucose levels by 49% and extract showed the best activity in the 150 th minute.